Complexity in Surfaces of Densest Packings for Families of Polyhedra - Engel, Michael; Chen, Elizabeth R.; Klotsa, Daphne; Damasceno, Pablo F.; Glotzer, Sharon C. (Physical Review X, 2014)
Packings of hard polyhedra have been studied for centuries due to their mathematical aesthetic and more recently for their applications in fields such as nanoscience, granular and colloidal matter, and biology. In all these fields, particle shape is important for structure and properties, especially upon crowding. Here, we explore packing as a function of shape. By combining simulations and analytic calculations, we study three two- parameter families of hard polyhedra and report an extensive and systematic analysis of the densest known packings of more than 55 000 convex shapes. The three families have the symmetries of triangle groups ( icosahedral, octahedral, tetrahedral) and interpolate between various symmetric solids ( Platonic, Archimedean, Catalan). We find optimal ( maximum) packing- density surfaces that reveal unexpected richness and complexity, containing as many as 132 different structures within a single family. Our results demonstrate the importance of thinking about shape not as a static property of an object, in the context of packings, but rather as but one point in a higher- dimensional shape space whose neighbors in that space may have identical or markedly different packings. Finally, we present and interpret our packing results in a consistent and generally applicable way by proposing a method to distinguish regions of packings and classify types of transitions between them.
Keywords: Materials Science; Soft Matter